2016
DOI: 10.1038/srep24436
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic transport of exosomes as a rapid route of information dissemination to the lymph node

Abstract: It is well documented that cells secrete exosomes, which can transfer biomolecules that impact recipient cells’ functionality in a variety of physiologic and disease processes. The role of lymphatic drainage and transport of exosomes is as yet unknown, although the lymphatics play critical roles in immunity and exosomes are in the ideal size-range for lymphatic transport. Through in vivo near-infrared (NIR) imaging we have shown that exosomes are rapidly transported within minutes from the periphery to the lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
141
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(151 citation statements)
references
References 49 publications
(63 reference statements)
4
141
0
1
Order By: Relevance
“…This property, and the fact that exosomes can carry small bits of genetic information make them potential therapeutic devices, possibly for future gene therapy approaches (913). Exosomes have been shown to preferentially enter lymphatic vessels and can be transported to lymph nodes within minutes (1016). The functional role may be to prime cells in the lymph node ahead of the arrival of antigen present cells or other immune cells (1016).…”
Section: New Directions: Microparticles Nanoparticles and Immunothementioning
confidence: 99%
“…This property, and the fact that exosomes can carry small bits of genetic information make them potential therapeutic devices, possibly for future gene therapy approaches (913). Exosomes have been shown to preferentially enter lymphatic vessels and can be transported to lymph nodes within minutes (1016). The functional role may be to prime cells in the lymph node ahead of the arrival of antigen present cells or other immune cells (1016).…”
Section: New Directions: Microparticles Nanoparticles and Immunothementioning
confidence: 99%
“…Control or Poly I:C exosomes (total quantity = 10 μg) were injected intradermally into the tail of eight-week-old male Balb/C mice (Charles River Laboratories, Wilmington, MA) as described previously18 and euthanized on day two (t = 48 hours). PBS was mixed with PEGylated IRdye 800CW (Licor) and injected similarly as the experimental control.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, we recently showed that exosomes are rapidly trafficked from peripheral tissues by the lymphatics, and retained in the draining lymph node by macrophages in a murine model18.…”
mentioning
confidence: 99%
“…47 Cancer cells in particular secrete large quantities of TEXs, which can be found in peripherally circulating blood. 48 Consequently, blood cells are exposed to many exosomes from both normal and malignant cells, 49 which play key roles in modulating the immune system.…”
Section: Discussionmentioning
confidence: 99%